Developing a Digital Video : Medical Students’ Experience During the COVID-19 Pandemic - Cheah, Whye Lian; Ayu Akida, Abdul Rashid; Helmy, Hazmi; Law, Leh Shii (Penerbit Universiti Sains Malaysia, 2023)
The study used a cross-sectional design to describe the production of video and perceptions of medical students during their Community Medicine and Public Health posting. A video on the COVID-19 was developed as part of students personalised and active online learning assignment during the movement control order (MCO) using the identify, conceptualise/connect, storyboard, develop, review/reflect/revise (ICSDR) development model. The study obtained student feedback via an online survey upon completing the video. A total of 39 students participated in the video production and online discussion. According to the respondents, the ICSDR model was useful in fostering their creativity in a structured manner and enabling more systematic learning. Additionally, their experiences were impactful and increased professionalism. The activity was authentic and fostered students’ decision-making for better teamwork and collaboration. The study is crucial as it addressed the healthcare needs of the local community aligned with the philosophy of the medical course, thus producing competent and compassionate graduates.